2019
DOI: 10.1016/j.avsg.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Daily Physical Activity and Sedentary Behavior of Claudicating Patients

Abstract: Our study objectively demonstrates the reduced physical activity of claudicating patients and documents physical activity/duration profiles throughout the day. The intensity of the physical activity of the average claudicating patient fluctuates very little during the day and rarely exceeds a light intensity level. Claudicating patients spend approximately half of their awake time in sedentary behavior and when they walk they do it in short bursts followed by several minutes of rest. We anticipate that changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 40 publications
4
36
3
Order By: Relevance
“…Previous studies found that patients with PAD have increased amount and altered temporal structure of gait variability compared with healthy controls [7,8]. Gait alterations in patients with PAD are consistently present prior to the onset of claudication pain and even from the initial steps of the patient when the oxygen levels in the legs have not been challenged yet [68,42]. Our current study is the first to attempt to dissect the potential contribution of reduced blood flow which many investigators feel is a key mechanism operating to produce the gait alterations of PAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies found that patients with PAD have increased amount and altered temporal structure of gait variability compared with healthy controls [7,8]. Gait alterations in patients with PAD are consistently present prior to the onset of claudication pain and even from the initial steps of the patient when the oxygen levels in the legs have not been challenged yet [68,42]. Our current study is the first to attempt to dissect the potential contribution of reduced blood flow which many investigators feel is a key mechanism operating to produce the gait alterations of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptom is intermittent claudication, a cramping pain that occurs in the calves, thighs and/or buttocks brought on by physical activity and relieved with rest. Patients with PAD are also significantly compromised by decreased physical activity and a higher prevalence of falls [46]. Advanced biomechanical evaluations have been undertaken to elucidate the mechanisms responsible for these problems [712].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common symptom is intermittent claudication, a cramping pain that occurs in the calves, thighs and/or buttocks brought on by physical activity and relieved with rest. Patients with peripheral artery disease who experience intermittent claudication (PAD-IC) are also significantly compromised by decreased physical activity and a higher prevalence of falls [4][5][6]. Advanced biomechanical evaluations have been undertaken to elucidate the mechanisms responsible for these problems [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced biomechanical evaluations have been undertaken to elucidate the mechanisms responsible for these problems [7][8][9][10][11][12]. The results of these works demonstrate that the gait changes are driven by pathophysiological alterations that occur long before intermittent claudication symptoms drive patients to see a physician for pain during walking [6,13,14].…”
Section: Introductionmentioning
confidence: 99%